MicroRNA‐570 is a novel regulator of cellular senescence and inflammaging. Issue 2 (29th August 2018) - Baker, Jonathan R.; Vuppusetty, Chaitanya; Colley, Thomas; Hassibi, Shyreen; Fenwick, Peter S.; Donnelly, Louise E.; Ito, Kazuhiro; Barnes, Peter J.
ABSTRACT: Diseases of accelerated aging often occur together (multimorbidity), and their prevalence is increasing, with high societal and health care costs. Chronic obstructive pulmonary disease (COPD) is one such condition, in which one half of patients exhibit ≥4 age‐related diseases. Diseases of accelerated aging share common molecular pathways, which lead to the detrimental accumulation of senescent cells. These senescent cells no longer divide but release multiple inflammatory proteins, known as the senescence‐associated secretory phenotype, which may perpetuate and speed disease. Here, we show that inhibiting miR‐570‐3p, which is increased in COPD cells, reverses cellular senescence by restoring the antiaging molecule sirtuin‐1. MiR‐570‐3p is induced by oxidative stress in airway epithelial cells through p38 MAP kinase‐c‐Jun signaling and drives senescence by inhibiting sirtuin‐1. Inhibition of elevated miR‐570‐3p in COPD small airway epithelial cells, using an antagomir, restores sirtuin‐1 and suppresses markers of cellular senescence (p16 INK4a, p21 Waf1, and p27 Kip1 ), thereby restoring cellular growth by allowing progression through the cell cycle. MiR‐570‐3p inhibition also suppresses the senescence‐associated secretory phenotype (matrix metalloproteinases‐2/9, C‐X‐C motif chemokine ligand 8, IL‐1β, and IL‐6). Collectively, these data suggest that inhibiting miR‐570‐3p rejuvenates cells via restoration of sirtuin‐1, reducing many of the abnormalities associated with cellular senescence.—Baker, J. R., Vuppusetty, C., Colley, T., Hassibi, S., Fenwick, P. S., Donnelly, L. E., Ito, K., Barnes, P. J. MicroRNA‐570 is a novel regulator of cellular senescence and inflammaging. FASEB J. 33, 1605–1616 (2019). www.fasebj.org